Simulation of 300 m Simon Amman flying on the base of his jump 233 m from Planica - Jost, B. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Ski flying became a very popular sport discipline. To date ski jumpers are able to fly over 230 m. The objective of the study was to simulate a 300 m length flight on the base of the 233 m long jump of Simon Amman participating in the final individual competition of the World Cup in Ski Flights at Planica in 2009 (HS215m).